Saprahan Tradition as Local Wisdom Embodies the Values of Cultured Islamic Education in West Kalimantan, Indonesia - Pratiwi Amalia Putri; Muhammad Adib Alfarisi; Ajeng Lestari; Mila Septian Haryati (UIN Syarif Hidayatullah Jakarta, 2024)
Socio-cultural issues are often interesting and unique with various problems occurring, such as deviations and divisions for the digital native generation with hedonism life without seeing the good and bad effects or factors that occur. This article aims to examine the values contained in the Saprahan tradition in terms of Islamic education and the relevance of the constitution in the 1945 Constitution, namely building the unity of the nation, the state experiencing the era of modernism. On the other hand, the authors use pierre bourdieu's theory of habitus that shapes the values and structure of people's social life. This study, with the work of collecting data, records, documents included in the library research technique analyzed using content analysis. The results of this study show that local wisdom has an adaptive ability in dealing with problems faced by human life. So that the authors argue that there are values and norms from local wisdom in the Saprahan tradition as a form of kinship in the community's cultural space. As with the Saprahan tradition, there is wejangan as diversity in the learning process by instilling the value of togetherness, unity, equality, mutual respect, eliminating ego, and strengthening the relationship between religions, ethnicities, groups, which maintains integrity and unity in the symbol of the Republic of Indonesia.